The sea route to Asia : the adventures of Portugese explorers, from Prince Henry the Navigator to Bartholomeu Dias and Vasco da Gama - Rutsala, David (Philadelphia : Mason Crest Publishers, 2003)
Discusses the quest of Portuguese explorers to find a route around Africa to Asia, focusing on the adventures of such famous leaders as Prince Henry the Navigator, Bartholomeu Dias, and Vasco da Gama.
Includes bibliographical references (p. 62) and index.
Keywords: Discoveries in geography -- Portuguese; Discoveries in geography; Explorers; East Indies -- Discovery and exploration -- Portuguese; East Indies -- Discovery and exploration -- Portuguese